(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
This study investigated the spatial variability of soil exchangeable basic cations along the River Wudil floodplain in Wudil Local Government Area, Kano State, Nigeria. A total of 150 soil samples were collected at a depth of 0â€“30 cm using a systematic 100 Ã— 200 m grid sampling technique. Calcium (Ca), Magnesium (Mg), Potassium (K), and Sodium (Na) were analyzed in the laboratory. Both classical and geostatistical methods, including semivariogram analysis and ordinary kriging, were employed to describe the properties and spatial correlation of the cations. The results revealed that Ca and Na exhibited strong spatial dependence, while Mg and K showed moderate spatial dependence. The variability was highest for calcium (39.4%) and lowest for sodium (16.7%), indicating considerable heterogeneity across the floodplain soils. This spatial variability suggests that uniform soil management practices may be inefficient for the area. Therefore, integrated soil fertility management through the combined use of organic and inorganic fertilizers is recommended to address nutrient imbalances. Additionally, site-specific nutrient management strategies should be developed to enhance resource use efficiency and crop productivity. Overall, the study demonstrates that geostatistical techniques are effective tools for assessing soil fertility status and guiding precision agriculture. Understanding the spatial distribution of soil cations is vital for sustainable land use planning and improved agricultural productivity in floodplain ecosystems.